Analisis Tingkat Kepuasan Pelanggan Terhadap Pelayanan Kefarmasian Di Apotek Keluarga 3 STIFAR - Rahmayati Rusnedy; Siti Hizra Alpatiqa; Siti Riani; Mira Febrina; Nofri Hendri Sandi; Hanifah Siti Aisyah (Jurnal Ners, 2025)
Pharmaceutical service analysis activities are needed to maintain existing excellence and consistently improve quality services in dimensions that are still lacking in assessment standards so that when the level of customer satisfaction has not been achieved, of course this will be an important focus for pharmacy management in order to improve the quality of satisfaction with services. The purpose of this study was to analyze the level of customer satisfaction with services at Apotek Keluarga 3 Stifar. This study is a retrospective study with a cross-sectional method with sampling that meets the criteria by purposive sampling of customers who buy medicine. This research instrument uses the Servqual Concept which will focus on 3 dimensions, including the dimensions of Responsiveness, Reliability and Empathy, in each of which 3 question points are arranged based on the form of service that has been provided by employees of the Pharmacy Family 3 Stifar Riau to customers. The evaluation results show the level of customer satisfaction responsiveness (responsiveness) is included in the very satisfied category (85%), Reliability (reliability) 84% is included in the Very Satisfied category and Empathy 87% (Very Satisfied). Based on the evaluation of customer satisfaction assessed based on the dimensions of Responsiveness, Reliability and Empathy, it is at the "Very Satisfactory" level, with an average value of the third dimension tested of 85%.